2013
DOI: 10.1159/000353181
|View full text |Cite
|
Sign up to set email alerts
|

Human Cardiovascular Disease IBC Chip-Wide Association with Weight Loss and Weight Regain in the Look AHEAD Trial

Abstract: Background/Aims: The present study identified genetic predictors of weight change during behavioral weight loss treatment. Methods: Participants were 3,899 overweight/obese individuals with type 2 diabetes from Look AHEAD, a randomized controlled trial to determine the effects of intensive lifestyle intervention (ILI), including weight loss and physical activity, relative to diabetes support and education, on cardiovascular outcomes. Analyses focused on associations of single nucleotide polymorphisms (SNPs) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
0
23
0
1
Order By: Relevance
“…The rs1402837 T allele (gene G6PC2 of chr 2) is known to be associated with blood sugar levels (glycated hemoglobin levels). McCaffery et al [2013] reported that SNPs in ABCB11 (like rs484066) of chr 2 are associated with weight loss and regain. Meta-analysis of several GWAS found rs17271305 (gene VPS13C of chr 15) to be associated with glucose levels 2 hours after an oral glucose challenge [Saxena et al, 2010].…”
Section: Resultsmentioning
confidence: 99%
“…The rs1402837 T allele (gene G6PC2 of chr 2) is known to be associated with blood sugar levels (glycated hemoglobin levels). McCaffery et al [2013] reported that SNPs in ABCB11 (like rs484066) of chr 2 are associated with weight loss and regain. Meta-analysis of several GWAS found rs17271305 (gene VPS13C of chr 15) to be associated with glucose levels 2 hours after an oral glucose challenge [Saxena et al, 2010].…”
Section: Resultsmentioning
confidence: 99%
“…We also genotyped 35 unrelated samples from the International HapMap Project ( n =15 for CEPH [Utah residents with ancestry from northern and western Europe; CEU]; n =4 for Han Chinese in Beijing, China [CHB]; n =4 for Japanese in Tokyo, Japan [JPT]; n =3 for Mexican ancestry in Los Angeles, California [MEX] and n =9 for Yoruba in Ibadan, Nigeria [YRI]) to serve as anchors in analyses of genetic ancestry. We removed samples that failed genotyping (>5% missing data), blind duplicate samples, samples displaying sex inconsistencies, and samples displaying a high degree of discordance with genotyping available from the Institute of Translational Medicine and Therapeutics (ITMAT)-Broad-CARe (IBC) CVD array [19]. This reduced the available sample size to 4,258.…”
Section: Methodsmentioning
confidence: 99%
“…After excluding SNPs in linkage disequilibrium (LD, r 2 > 0.3), EIGENSTRAT was used to compute principal components (PCs) for use as covariates to control for population admixture in the regression analyses (26). …”
Section: Methodsmentioning
confidence: 99%